2019
DOI: 10.1177/0300060519882221
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan in reversing worsening acute heart failure: A systematic review and meta-analysis

Abstract: ObjectiveIn this meta-analysis, we aimed to compare efficacy and clinical outcomes of tolvaptan in treating acute heart failure (AHF).MethodsUsing MEDLINE, we searched relevant clinical studies using tolvaptan that investigated clinical effects in treating AHF. We performed meta-analysis for potentially extractable clinical outcomes such as body weight reduction, change in serum sodium levels, and clinical or safety events including worsening heart failure, worsening renal function (WRF), all-cause mortality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
3
8
0
2
Order By: Relevance
“… 8 , 9 , 10 , 11 We found no significant difference in change in creatinine between the two groups. Our results in conjunction with a recent meta-analysis by Wang, et al which concluded that add-on tolvaptan significantly reduced the risk of worsening renal failure 6 suggests that tolvaptan has no significant detrimental effect on renal function. Further, tolvaptan can be used in patients with creatinine clearance of up to 10 ml/min.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“… 8 , 9 , 10 , 11 We found no significant difference in change in creatinine between the two groups. Our results in conjunction with a recent meta-analysis by Wang, et al which concluded that add-on tolvaptan significantly reduced the risk of worsening renal failure 6 suggests that tolvaptan has no significant detrimental effect on renal function. Further, tolvaptan can be used in patients with creatinine clearance of up to 10 ml/min.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings are consistent with the previous meta-analysis studies. 6 , 7 Like the prior studies including the EVEREST trial, our study concluded that add-on tolvaptan therapy significantly increased serum sodium levels compared to the standard diuretic therapy. 8 , 9 , 10 , 11 We found no significant difference in change in creatinine between the two groups.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…У пациентов с нормальным или повышенным системным артериальным давлением эффективной может быть комбинация диуретиков с вазодилататорами, из которых наиболее перспективным выглядит применение серелаксина (рекомбинантный аналог человеческого релаксина-2), низких доз несиритида (рекомбинантный человеческий мозговой наутрийуретический пептид) и антагониста вазопрессина толваптана (особенно при гипонатриемии разведения) [63,65,66]. Наконец, сдвинуть процесс с мертвой точки и достигнуть заветной эуволемии при рефрактерном отечном синдроме может помочь применение в составе комбинированной терапии препаратов из группы ингибиторов натрийзависимого котранспортера глюкозы 2-го типа (например, дапаглифлозина или эмпаглифлозина) [63,67,68].…”
Section: долгосрочная стратегия леченияunclassified
“…While the effectiveness of TLV for ADHF treatment has been well established, long-term TLV administration for CHF treatment remains controversial. Although several recent studies have demonstrated the usefulness of TLV in patients with CHF, most of them had a small sample size and were observational studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Furthermore, the cost of TLV is much higher than that of other conventional drugs for HF treatment; however, no study has investigated the cost-effectiveness of long-term TLV administration for CHF treatment in Japan.…”
Section: Introductionmentioning
confidence: 99%